Developing Interactive English Learning Media Based ICT for Elementary Student - Mukhlisin Mukhlisin; A. Wathon (EDUCATIO: Journal of Education)
The implementation of information and communication technology (ICT) curriculum at elementary school is the educational sector development. ICT subject is a practical subject which requires a direct practice to make easier in elementary student understanding the material. Founding many problems in understanding their English material especially reading comprehension a teacher is demanded to make a learning media which helps the student to understand the material of study. This research is aimed at describing the model of ICT in elementary school and using of learning media. Moreover, the description can be bocome one of the basic from the development of interactive study model base on student self learning. Designing material for elementary student and giving media learning can motivate them in teaching learning English better. Concerning these problems, a set of suitable instructional elementary student material and media learning for elementary student. Besides, the arranging of this study model is hoped to make habitual and self-learning.